Malawi phases out harmful pesticide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Malawi is well on target to eliminate methyl bromide by the end of 2005, ahead of the 2015 deadline for developing countries.